(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Dyrda I. A. Principles of studying Ukrainian as a foreign language: problems of theory. The paper accentuates the essence of the term “principles of education”, the views of Ukrainian and foreign scientists concerning different principles of education are analyzed. The paper marks out general didactical and linguistic didactical principles of studying Ukrainian as a foreign language.